Measuring the effect of student loans on the college dropout rate - Alex Solis (Uppsala University, Department of Economics, 2019)
Most governments around the world offer student loans to help disadvantaged students to enroll in college to reduce the attainment gap between rich and poor. However, we know little about the consequences of these loans. The reduction of the gap depends not only on initial enrollment but also on the dropout rate before graduation. This paper shows how the availability of loans affects the dropout rate in college. Two programs in Chile assign loans based on a cutoff in the national college admission test, enabling a regression discontinuity design. The analysis uses on students who were not induced by the loan to enroll in the first year. I show that access to loans reduces the dropout rate by 25 percentage points and is highly persistent over time (up to the fifth year after initial enrollment). At the cutoff, access to loans allows eliminating the differences in the dropout rate by family income. Finally, I find that students are not sensitive to tuition costs when loans are available.
urn:nbn:se:uu:diva-391965
Keywords: 330